Air quality and climate change: Designing new win-win policies for Europe. Issue 65 (November 2016) - Maione, Michela; Fowler, David; Monks, Paul S.; Reis, Stefan; Rudich, Yinon; Williams, Martin L.; Fuzzi, Sandro
Highlights: Anthropogenic emissions cannot be unambiguously separated in atmospheric pollutants and climate-forcers. Policy measures to mitigate air quality and climate change must necessarily be integrated. Methods to achieving emission reductions of GHGs will be as important as the commitments themselves. Abstract: Anthropogenic activities are responsible for the emission of gaseous and particulate pollutants that modify atmospheric composition. Such changes are, in turn, responsible for the degradation of air quality at the regional/local scale as well as for changes of climate. Air pollution and climate change are two intimately connected environmental issues. However, these two environmental challenges are still viewed as separate issues, which are dealt with by different science communities and within different policy frameworks. Indeed, many mitigation options offer the possibility to both improve air quality and mitigate climate change but, at the same time, mitigation options that may provide benefits to one aspect, are worsening the situation in the other. Therefore, coordinated actions taking into account the air quality-climate linkages are required. These actions need to be based on strong scientific grounds, as recognised by the European Commission that in the past few years has promoted consultation processes among the science community, the policy makers and the relevant stakeholders. Here, the main fields in which such coordinated actions are needed are examined from a policy perspective.